2017
DOI: 10.1007/s00128-017-2252-x
|View full text |Cite
|
Sign up to set email alerts
|

Applying Incremental Sampling Methodology to Soils Containing Heterogeneously Distributed Metallic Residues to Improve Risk Analysis

Abstract: This study compares conventional grab sampling to incremental sampling methodology (ISM) to characterize metal contamination at a military small-arms-range. Grab sample results had large variances, positively skewed non-normal distributions, extreme outliers, and poor agreement between duplicate samples even when samples were co-located within tens of centimeters of each other. The extreme outliers strongly influenced the grab sample means for the primary contaminants lead (Pb) and antinomy (Sb). In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Range 4-3 is used by Army National Guard units for training with small-arms weapons systems, such as the M16 Rifle that fires a 4.5 cm long by 5.56 mm diameter (caliber) projectile round. Clausen et al [9,11] present additional information on the characteristics of the range. Camp Ethan Allen has a temperate climate with warm, humid summers and cold winters.…”
Section: Soil Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Range 4-3 is used by Army National Guard units for training with small-arms weapons systems, such as the M16 Rifle that fires a 4.5 cm long by 5.56 mm diameter (caliber) projectile round. Clausen et al [9,11] present additional information on the characteristics of the range. Camp Ethan Allen has a temperate climate with warm, humid summers and cold winters.…”
Section: Soil Sample Collectionmentioning
confidence: 99%
“…Clausen et al [9] demonstrated a large number of grab samples (n > 35 at a minimum and preferably as many as several hundred) would be needed to address the large degree of spatial variability on small-arms ranges. The high uncertainties in metal concentrations associated with grab samples propagate to calculated exposure point concentrations used in risk assessments [11].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the manufacturer could use the Decision Framework to support and record their decision that use of the wastewater treatment system to treat wastewater containing the new explosive was an unacceptable risk and could not continue without mitigation (Figure 2). proven approaches such as multi-increment sampling that is designed to provide high confidence results (46). Laboratory analysis was conducted using proven techniques such as the EPA8330B extraction method, and robust soil preparation methods (47,48).…”
Section: Stagementioning
confidence: 99%
“…Owing to the limitations of conducting toxicological health risk assessments in a population, the Monte Carlo simulation (mathematical and logical model) has been widely used in recent years. It was used to understand the behavior of water systems by assuming different problems and systems, showing an advantage over experiments ( Clausen et al, 2017 ; Sasaki et al, 2017 ). Moreover, the Monte Carlo simulation of uncertainties was applied in the risk assessment model by collecting limited samples to predict the overall situation.…”
Section: Introductionmentioning
confidence: 99%